A mitogenomic approach to the taxonomy of pollocks. Theragra chalcogramma and T. finnmarchica represent one single species - Ursvik, Anita; Breines, Ragna; Christiansen, Jørgen Schou; Fevolden, Jan-Erik; Coucheron, Dag H.; Johansen, Steinar D. (BMC Evolutionary Biology, 2007)
Background: The walleye pollock (Theragra chalcogramma) and Norwegian pollock (T. finnmarchica) are confined to the North Pacific and North Atlantic Oceans, respectively, and considered as distinct species within the family Gadidae. We have determined the complete mtDNA nucleotide sequence of two specimens of Norwegian pollock and compared the sequences to that of 10 specimens of walleye pollock representing stocks from the Sea of Japan and the Bering Sea, 2 specimens of Atlantic cod (Gadus morhua), and 2 specimens of haddock (Melanogrammus aeglefinus). Results: A total number of 204 variable positions were identified among the 12 pollock specimens, but no specific substitution pattern could be identified between the walleye and Norwegian pollocks. Phylogenetic analysis using 16.500 homologous mtDNA nucleotide positions clearly identify the Norwegian pollock within the walleye pollock species cluster. Furthermore, the Norwegian pollock sequences were most similar to mitochondrial genotypes present in walleye pollock specimens from the Sea of Japan, an observation supported both by neighbor-joining, maximum parsimony, and maximum likelihood analyses. Conclusion: We infer that walleye pollock and Norwegian pollock represent one single species and that Norwegian pollock has been recently introduced from the Pacific to the Atlantic Oceans.